Parliament of man: the past, present and future of the United Nations - "Kennedy, Paul" (New York, 2007)
Paul Kennedy's The Parliament of Man: The United Nations and the Quest for World Government is the extraordinary story of the UN - its creation, the threats it has faced, and the possibilities it holds for the future. Can the world be governed by agreement rather than conflict? In 1945 the world's most powerful nation states came together to 'save succeeding generations from the scourge of war and reaffirm faith in the fundamental human rights'. Over sixty years later, the United Nations still doggedly pursues that mandate. Paul Kennedy's The Parliament of Man is a timely history that examines the roots and functions of this unique organization, casts an objective eye on its past effectiveness and assesses whether it will meet the challenges of our present world - from supplying aid during humanitarian crises to combating climate change. Ultimately he shows why, despite its fallibility and its foibles, the UN remains utterly indispensable to our future. 'Wonderful ... a highly readable and sophisticated account' Independent 'Extraordinary ... a retelling of the United Nations story to remind us why it remains a necessary organisation' The New York Times 'A sweeping historical tour ... this is a necessary book' Financial Times 'Masterful' New Statesman 'Appealing ... Accessible ... never loses sight of the larger truth' Tony Judt, New York Review of Books Paul Kennedy is a Professor of History at Yale University. He took his doctorate in Oxford and began work shortly afterwards for the first great historian of the Second World War, Sir Basil Liddell Hart. Kennedy is the author or editor of nineteen books, including The Rise and Fall of the Great Powers, which has been translated into over twenty languages, Preparing for the Twenty-First Century, The Parliament of Man and the now classic Rise and Fall of British Naval Mastery.
Keywords: United Nations-History